Clinical and symptom scores are significantly correlated with fecal microbiota features in patients with symptomatic uncomplicated diverticular disease: a pilot study. Issue 1 (January 2018) - Kvasnovsky, Charlotte L.; Leong, Lex E.X.; Choo, Jocelyn M.; Abell, Guy C.J.; Papagrigoriadis, Savvas; Bruce, Kenneth D.; Rogers, Geraint B.
Abstract : Background: There is growing consensus that symptomatic uncomplicated diverticular disease is a chronic inflammatory condition, and that alterations in the fecal microbiota may contribute to its pathogenesis. Objective: The aim of this study was to relate the fecal microbiota composition in symptomatic uncomplicated diverticular disease to measures of inflammation, symptoms, and history of previous acute diverticulitis. Participants and methods: Fecal microbiota composition in 28 individuals with symptomatic uncomplicated diverticular disease was characterized by 16S RNA gene amplicon sequencing. Microbiota composition was related to clinical history, symptom and inflammation measures, and demographic variables. Results: Previous acute diverticulitis was associated with higher relative abundance of Pseudobutyrivibrio, Bifidobacterium, Christensenellaceae family, and Mollicutes RF9 order ( P =0.004, 0.006, 0.010, and 0.019, respectively), but not microbiota alpha or beta diversity. A higher bloating severity score was significantly correlated with a higher relative abundance of Ruminococcus ( P =0.032), and significantly inversely correlated with the relative abundance of the Roseburia ( P =0.002). Fecal calprotectin levels were positively correlated with alpha diversity (Shannon index, P =0.005) and the relative abundance of Lactobacillus ( P =0.004). Pain score was positively correlated with the relative abundance of Cyanobacterium (adjusted P =0.032). Conclusion: Patient symptoms in symptomatic diverticular disease are significantly correlated with features of the fecal microbiota. Our findings suggest the potential utility of therapies that target intestinal microbiology, such as dietary prebiotic supplements. Abstract : Supplemental Digital Content is available in the text.